Inovasi Ice Gel Ekonomi Sebagai Pengganti Es Batu Untuk Nelayan di Pesisir Mamburungan Tarakan - Theresia, Theresia; Mumtaza Putri, Anne; Yulianto, Agus; Andriyanto, Andriyanto; Haikal, Muhammad; Gandri Haryono, M.; Indrawanto, Denny; Warol, Warol (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
The "Economic Ice Gel Innovation as an Alternative to Ice Blocks for Fishermen in the Coastal Area of Mamburungan, Tarakan" aims to address the challenges faced by local fishermen in preserving the freshness of their catch. The conventional ice blocks currently in use have limitations, such as melting quickly and high costs, making them inefficient for long-term storage. The economic ice gel innovation presents a more effective and economical alternative. Ice gel can maintain cold temperatures for longer periods, does not melt easily, and can be reused multiple times, thereby reducing fishermen's operational costs. This program involves research and development of suitable ice gel, training for fishermen on its usage, and monitoring and evaluation of the technology's implementation. A participatory approach is used to ensure that the solutions provided meet local needs. This innovation is expected to improve storage efficiency, reduce quality loss of fish, and support the welfare of fishermen in Mamburungan. Additionally, the use of ice gel has positive environmental impacts by reducing the production and disposal of ice blocks. The program is anticipated to make a significant contribution to increasing fishermen's income and quality of life, as well as the sustainability of fishery resources.